Features of a condition of endometrium against preope rative medical training of patients with uterine myoma - A. N. Plekhanov; Iu S. Shishkina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The key moments of pathogenesis of uterine myoma, influence of steroid hormones and their receptors on regulation of growth of uterine myoma are reflected in the article, thepreparations used for preoperative training of patients with uterine myomaand peculiarities of their impact on endometrium are analyzed